Effect of radiation exposure on survival after first solid cancer diagnosis in A-bomb survivors. (April 2023) - Sposto, Richard; Sugiyama, Hiromi; Tsuruyama, Tatsuaki; Brenner, Alina V.
Abstract: Background: Comparison of the estimated effect of atomic bomb radiation exposure on solid cancer incidence and solid cancer mortality in the RERF Life Span Study (LSS) reveals a difference in the magnitude and shape of the excess relative risk dose response. A possible contributing factor to this difference is pre-diagnosis radiation effect on post-diagnosis survival. Pre-diagnosis radiation exposure theoretically could influence post-diagnosis survival by affecting the genetic makeup and possibly aggressiveness of cancer, or by compromising tolerance for aggressive treatment for cancer. Methods: We analyze the radiation effect on post-diagnosis survival in 20, 463 LSS subjects diagnosed with first-primary solid cancer between 1958 and 2009 with particular attention to whether death was caused by the first-primary cancer, other cancer, or non-cancer diseases. Results: From multivariable Cox regression analysis of cause-specific survival, the excess hazard at 1 Gy (EH1Gy ) for death from the first primary cancer was not significantly different from zero – p = 0.23, EH1Gy = 0.038 (95 % CI: −0.023, 0.104). Death from other cancer and death from non-cancer diseases both were significantly associated with radiation dose: other cancer EH1Gy = 0.38 (95 % CI: 0.24, 0.53); non-cancer EH1Gy = 0.24 (95 % CI: 0.13, 0.36), both p < 0.001. Conclusion: There is no detectable large effect of pre-diagnosis radiation exposure on post-diagnosis death from the first primary cancer in A-bomb survivors. Impact: A direct effect of pre-diagnosis radiation exposure on cancer prognosis is ruled out as an explanation for the difference in incidence and mortality dose response in A-bomb survivors. Highlights: Analysis of survival of 20, 000 + atomic bomb survivors diagnosed with solid cancer. A-bomb radiation exposure prior to a cancer diagnosis does not influence survival from the primary diagnosed cancer. A-bomb radiation exposure prior to cancer diagnosis does influence survival for non-primary cancer death causes. Radiation influence on solid cancer prognosis does not contribute to the difference in mortality and incidence dose response.